Sunitinib in Metastatic Renal Cell Carcinoma: A Systematic Review of UK Real World Data - Argyropulo-Palmer, Miriam; Jenkins, Aaron; Theti, Davinder Singh; Larkin, James; Montgomery, David (Frontiers in Oncology, 2015)
Background Real world data are increasingly used to inform drug reimbursement decisions, but it is unclear how well outcomes from real world studies compare to those of clinical trials. This systematic review seeks to compare outcomes for sunitinib in routine UK clinical practice with the sunitinib registrational and expanded access program clinical trials. Method Systematic review of the real world published literature was undertaken. UK observational studies recording first or second line sunitinib efficacy were included. A qualitative summary of the results and comparison to the controlled clinical trials was conducted. 15 real world studies were included, 14 of which were only available as posters/presentations. Results Real world study reporting quality was generally low, making comparisons with the clinical trials difficult. Practice relating to starting dose, dose modification, timing of therapy initiation and other factors varied between centres. Median progression free survival and adverse events were generally comparable to the clinical trial outcomes, but overall survival was not. Conclusions There are few published data on sunitinib use in UK clinical practice. Studies are characterised by lack of peer reviewed publication and heterogeneity in design, reporting and analysis. For use of real world data in the reimbursement setting, data collection and reporting will need to improve.